2021
DOI: 10.1111/1756-185x.14114
|View full text |Cite
|
Sign up to set email alerts
|

Secukinumab and metformin ameliorate dermal fibrosis by decreasing tissue interleukin‐17 levels in bleomycin‐induced dermal fibrosis

Abstract: Although the pathogenesis of systemic sclerosis is not exactly known, it is thought that immune activation has prominent roles in pathogenesis. Secukinumab is a monoclonal antibody against interleukin (IL)‐17A. Metformin, a widely used antidiabetic medication, has anti‐proliferative, immunomodulating and anti‐fibrotic activities. The purpose of our study is to determine the therapeutic efficacy of secukinumab and metformin on bleomycin (BLM) induced dermal fibrosis. Fifty Balb/c female mice were divided into 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 50 publications
(57 reference statements)
0
12
0
Order By: Relevance
“…Karatas et al. reported that secukinumab and metformin ameliorated dermal fibrosis in bleomycin-induced mouse models by decreasing dermal thickness and tissue IL-17A levels, suggesting the association of IL-17A with dermal fibrosis in animals ( 40 ). However the pro-fibrotic mechanisms of IL-17A in animal models cannot be applied to humans ( 1 ).…”
Section: Il-17 and Systemic Sclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…Karatas et al. reported that secukinumab and metformin ameliorated dermal fibrosis in bleomycin-induced mouse models by decreasing dermal thickness and tissue IL-17A levels, suggesting the association of IL-17A with dermal fibrosis in animals ( 40 ). However the pro-fibrotic mechanisms of IL-17A in animal models cannot be applied to humans ( 1 ).…”
Section: Il-17 and Systemic Sclerosismentioning
confidence: 99%
“…One possible reason this anti-fibrogenic effect of IL-17A is not capable of containing the fibrosis in SSc could be that intrinsic differences between normal and SSc fibroblasts show that SSc fibroblasts are more resistant than their normal counterparts in response to collagen inhibition under the influence of IL-17. This property of SSc fibroblasts may help them escape or limit the anti-fibrotic effects of IL-17 ( 40 ).…”
Section: Il-17 and Systemic Sclerosismentioning
confidence: 99%
“…Therapeutic effects of metformin were also investigated in Sjögren’s syndrome [ 111 ], scleroderma [ 112 115 ], ankylosing spondylitis [ 116 ], and gout [ 117 ]. Metformin reversed salivary gland inflammation and hypofunction in murine Sjögren’s syndrome by controlling imbalanced T and B cell differentiation [ 111 ].…”
Section: Therapeutic Effects Of Metformin In Other Autoimmune Inflammatory Rheumatic Diseasesmentioning
confidence: 99%
“…Metformin reversed salivary gland inflammation and hypofunction in murine Sjögren’s syndrome by controlling imbalanced T and B cell differentiation [ 111 ]. To examine the effects of metformin on scleroderma, a mouse model of bleomycin-induced skin fibrosis was employed [ 112 115 ]. Metformin attenuated skin fibrosis in mice, as evidenced by reductions in skin thickness, collagen deposition, and numbers of myofibroblasts.…”
Section: Therapeutic Effects Of Metformin In Other Autoimmune Inflammatory Rheumatic Diseasesmentioning
confidence: 99%
“…Park, et al also reported on the efficacy of targeting IL-17 in bleomycin-induced mice and chronic graft-versus-host disease models ( 105 ). Using Secukinumab, a monoclonal antibody against IL-17A, Karatas, et al showed the amelioration of bleomycin-induced dermal fibrosis in mice ( 106 ). In humans, an active but not recruiting phase III trial of brodalumab (AMG 827), a human, anti-IL17 receptor monoclonal antibody, for SSc (Clinicaltrials.gov identifier: NCT03957681 ) is undergoing.…”
Section: Imbalance Of Treg Cells and Th17 Cells In Sscmentioning
confidence: 99%